PENGARUH PEMBERIAN PROBIOTIK DARI MIKROBA LOKAL TERHADAP KUALITAS INDEKS ALBUMEN, INDEKS YOLK, DAN WARNA YOLK PADA UMUR TELUR 10 HARI - Arista Pribadi; Tintin Kurtini; Sumardi . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The purpose of this research were to know 1) the effect of probiotic local microbial to quality of albumen index, yolk index and yolk color; 2) the optimal of probiotic level in feed against to albumen index, yolk index and yolk color. The research was conducted on December 20th 2014– January 19th 2015 in CV.Varia Agung Jaya , Varia Agung Village, Seputih Mataram Sub district, Central Lampung regency. Manufacture of probiotic from local microbial was made on 8 to 19 December 2014 at the Laboratory of Microbiology Faculty, University of Lampung. This research used completely randomized design (CRD) with four probiotic treatments of local microbial (0%, 1%, 2% and 3%) with 5 replications and use 40 layers. The data were analyzed with the assumptions of variance. Based on these result it can be concluded that probiotic local microbial (0%, 1%, 2% and 3%) was not significant (P> 0.05) on the quality of albumen index, yolk index and yolk color. (Keywords: Probiotic, Albumen index, Yolk index and Yolk color).